Experimental and Theoretical Study on the Freshwater Productivity of a Single-Slope Solar Still - Tugan, Volkan; Isik, Erdem; Inalli, Mustafa (Wiley, 2025)
Converting saline water into freshwater using renewable energy resources is crucial to address global shortages of freshwater. This study aims to investigate the freshwater productivity of a single-slope solar still (SSS) operating with solar energy, one of the renewable energy sources. The main motivation of this study is to evaluate the experimental, theoretical, and economic performance of the solar still under climate conditions that have not been sufficiently studied before. Experimental analyses were conducted under the climatic conditions of Tunceli, a city located in the Eastern Anatolia Region of T & uuml;rkiye. In addition, a comprehensive theoretical analysis was carried out using energy equations, and the experimental and theoretical results were compared with each other. Finally, the economic feasibility of the system was evaluated through a cost analysis. The SSS's experimental and theoretical productivity were found to be 1883.9 and 2458.7 g/m(2)/day, respectively. The experimental thermal efficiency for this still was 15.1%, whereas the theoretical thermal efficiency was 19.7%. It was concluded that the theoretical productivity and efficiency values were close to the experimental values and the difference between them originated from the assumptions of theoretical calculations. The cost of water distilled by the single-slope solar distillation unit was found to be $0.077/kg, and the payback period was found to be 9 months.
Keywords: freshwater productivity; solar still; thermal efficiency